(untitled) (Bangladesh Journal of Neuroscience, 2018)
Background: Epilepsy is a common chronic neurological disorder worldwide. Carbamazepine is one of the most commonly used antiepileptic drugs. It is a hepatic cytochrome P 450 enzyme inducer which is thought to cause alteration of serum lipids. Objective: To evaluate the effect of carbamazepine on serum cholesterol and atherogenic ratios in young adult epileptic patients. Materials and methods: This prospective study was conducted in the epilepsy clinic and Neurology OPD of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from December, 2017 to March, 2019. A total fifty seven newly diagnosed epileptic patients fulfilling the study criteria were studied. Serum TC, HDL-C, TG was measured by using Beckman Coulter- AU680 analyzer machine and LDL-C was calculated according to the Friedewald formula in the laboratory of Department of Biochemistry, BSMMU. Results: The mean (±SD) serum TC, LDL, TG, TC/HDL-C and LDL-C/HDL-C were significantly increased (p-value < 0.001) at 3 months of carbamazepine therapy in comparison to the baseline levels. The mean (±SD) serum HDL was decreased at 3 months of therapy which was not statistically significant (p-value: 0.135). Conclusion: Carbamazepine caused significant rise in serum TC, LDL-C, TG and atherogenic ratios (TC/HDL-C, LDL-C/HDL-C), and insignificant reduction in the serum HDL-C level after three months of therapy. Bangladesh Journal of Neuroscience 2018; Vol. 34 (1): 32-38